World oil prices changes and economic growth : case of Malaysia / Shaliza Azreen Mohd Zulkifli - Mohd Zulkifli, Shaliza Azreen (Research Management Institute (RMI), 2009)
The main objective of this study is to examine the impact of world oil price changes on Malaysian economic performance using multiple regression analysis on seven variables over the 60 months period starting from year 2003 to 2007. The variables used are inflation rate and Industrial Production Index; as dependent variables; interest rate, world oil price, oil export, net export, Bursa Malaysia Composite Index and Industrial Production Index t-1; as independent variables. Two models are formed from these variables. The results show that Industrial Production has significant relationship with its dependent variables. However, variables net export is dropped from the model due to the multicollinearity problem and the model is regressed again. Inflation rate also has significant relationship with its dependent variables.